Towards More Robust Self-Regulation Within the Legal Profession - Veronica Root Martinez; Caitlin Jean Juricic (Washington University Journal of Law and Policy, 2022)
The Trump Administration left reverberations throughout American life, and the legal profession was not insulated from its impact. The conduct of lawyers—both public and private—working on behalf of former President Trump was the subject of constant conversation and critique. The reality, however, is that the questions regarding the conduct of the Trump Administration lawyers, are rooted, in part, in more fundamental questions about the appropriate role of the lawyer within society. This Essay advocates for the adoption of a self-regulation scheme whereby lawyers regulate and oversee the conduct of other lawyers, to ensure that members of the legal profession are unwavering in their pursuit of the public good. The legal profession has long been charged with regulating its own members, but its failures in this regard have been both deep and profound. This Essay urges the legal profession to turn towards much more robust regulation of its members. There can be no collective pursuit of the public good by the legal profession without the collective will to sanction those who fail to adhere to its pursuit.
Keywords: Trump Administration; Trump; President; Legal profession; Conduct; Critique; Society; Self-Regulation; regulation; Profession; Sanction; Regulate